CULTURE AND SENSITIVITY PATTERN IN PATIENTS WITH EXTERNAL VENTRICULAR DRAIN INFECTION - Rafiq, Mirza Faisal Ahmed; Ahmed, Noor; Ali, Shafqut; Khan, Muhammad Naseem; Zaman, Khaleeq -uz- (Journal of Ayub Medical College Abbottabad, 2011)
Background: External ventricular (EVD) is a life saving procedure and involves insertion of a catheter in ventricular space to drain cerebrospinal fluid (CSF). Our objective of this study was to determine the culture and sensitivity (C/S) pattern in patients with EVD infection. Methods: This cross sectional study was conducted in Department of Neurosurgery, Pakistan Institute of Medical Sciences (PIMS), Islamabad from December 1, 2008 to January 31, 2010. All admitted patients who had acute hydrocephalus, underwent EVD insertion after excluding meningitis and ventriculitis by physical examination and per operative CSF sampling. The EVD was done at right Kocher’s point. Prophylactic third generation antibiotic (Ceftriaxone) was started and continued till EVD was in place. C/S was sent to PIMS laboratory on first documented fever and or change of CSF color or when plan was to replace EVD with Ventriculo-peritoneal shunt (VP). Once infection was there CSF was sent for C/S initially and routine examination (R/E) daily. Antibiotics were changed according to C/S report and continued till they were needed. Infection rate was also estimated. Results: Among 76 patients 41 (53.9%) were male and 35 (46.1%) were females. Most were adults and were between 31 to 40 years of age. Mean duration of EVD was 11.41 days. Overall infection rate was 11.8%. Among causative organisms Staphylococcus Aureus (44.4%) was most common followed by Acenitobacter and Enterobacter and commonly used prophylactic antibiotic (Ceftriaxone) had considerable resistance. Conclusion: EVD is a simple and life saving procedure. Most common organisms causing infection are Staphylococcus Aureus followed by Acenitobacter. Conventional used antibiotic Ceftriaxone has considerable resistance. Keywords: External Ventricular Drain, organisms, antibiotics